Transcriptomic and Proteomic Analyses Provide Insight into Sugar Metabolism-Induced Dormancy Release of Flower Buds of Pyrus pyrifolia ‘Cuiguan’ - Huiquan Wang; Ling Ding; Qinghua Ye; Xueying Huang; Lei Xu; Shaohua Wu; Dongjin He (Horticulturae, 2025)
Pear buds exhibit inherent dormancy, during which carbohydrates play a pivotal role in dormancy release and germination. In this study, Pyrus pyrifolia ‘Cuiguan’ was employed as the experimental material to investigate the molecular mechanisms underlying flower bud dormancy release. The results revealed that the dynamic balance between starch and soluble sugar is critical for promoting dormancy release and germination in P. pyrifolia ‘Cuiguan’ flower buds. Through transcriptomic and proteomic profiling, a total of 4035 differentially expressed genes (DEGs) and 1596 differentially expressed proteins (DEPs) were identified, which were predominantly associated with carbohydrate metabolism, particularly sugar metabolism pathways. Their changes were coordinately regulated at both transcriptional and translational levels. Key structural genes involved in maltose and sucrose biosynthesis, including BAM (LOC103949270), AAM (LOC125479337, LOC103940334, and LOC103941903), SPS (LOC125475683), and INV (LOC125478747), were significantly upregulated during the germination stage, facilitating flower bud sprouting. Integrated multi-omic analysis demonstrated that starch–sugar interconversion may govern dormancy release and sustained bud growth by modulating sugar metabolism-related genes and proteins. These findings provide novel insights into the molecular mechanisms of carbohydrate biosynthesis and associated protein regulation during dormancy release and development of P. pyrifolia ‘Cuiguan’ under natural conditions.